(3eaJGM JdNjU GdeaJGMs - (3GdNdNGdi eMeO Hf eXaQ GdNdNGdis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s ((3ESeGYjd Hf ESMGb Hf Ydi s)
(3ChdgG (B:s
(3CeG HYO aEf Chdi eG jTJZd Hg Gdgee gh Yde GdHdGZI s
(3BNQgG (B:s
(3Ydi CMSf hLhg GdHdGZI hGdaUGMI hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs